2015
DOI: 10.3174/ajnr.a4395
|View full text |Cite
|
Sign up to set email alerts
|

Enlargement of the Internal Auditory Canal and Associated Posterior Fossa Anomalies in PHACES Association

Abstract: SUMMARY:We noted enlargement of the internal auditory canal in several of our patients with posterior fossa malformations, hemangiomas, arterial anomalies, cardiac defects, eye abnormalities, and sternal or supraumbilical defects (PHACES) association and hence evaluated children with PHACES for the presence of an enlarged internal auditory canal and potential associated findings, including infantile hemangioma within the internal auditory canal, to understand the genesis of this enlargement. We reviewed our re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
2
6
0
Order By: Relevance
“…Judd et al 12 reported on the association between PHACES and intracranial hemangiomas. Most commonly described in the cerebellopontine angle or IAC, hemangiomas centered in or extending to Meckel cave both have been described in the literature 12,13 and noted in our series. One Metzler et al 13 similarly raised the possibility of a causal association between IAC hemangioma and IAC enlargement.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…Judd et al 12 reported on the association between PHACES and intracranial hemangiomas. Most commonly described in the cerebellopontine angle or IAC, hemangiomas centered in or extending to Meckel cave both have been described in the literature 12,13 and noted in our series. One Metzler et al 13 similarly raised the possibility of a causal association between IAC hemangioma and IAC enlargement.…”
Section: Discussionsupporting
confidence: 66%
“…Most commonly described in the cerebellopontine angle or IAC, hemangiomas centered in or extending to Meckel cave both have been described in the literature 12,13 and noted in our series. One Metzler et al 13 similarly raised the possibility of a causal association between IAC hemangioma and IAC enlargement. This was based on the increased prevalence of IAC hemangiomas within the enlarged IACs in children when imaged at younger than 1 year of age, compared with children older than 1 year of age at initial imaging, in whom the hemangiomas were presumed to have previously involuted.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…There is a high incidence of a funnel-shaped enlarged internal auditory canal, many of which have a hemangioma within their enlarged structure. 11,[27][28][29] Dandy-Walker malformation (which is characterized by vermian hypoplasia, cystic dilatation of the fourth ventricle, and an enlarged posterior fossa with torcular-lambdoid inversion) is the most common posterior fossa malformation associated with PHACES syndrome. Large cervicofacial hemangiomas are the hallmarks of PHACES, classically with a segmental distribution.…”
Section: Imaging Of Rich and Nichmentioning
confidence: 99%